Intervention Strategies: Cognition, Behavior, and Intellectual Disabilities - Macešic-Petrovic, Dragana; Kovacevic, Jasmina; Hasanbegovic, Husnija (Highlights on Medicine and Medical Research Vol. 15, 2021)
Introduction: The study is part of wider research project, published as article based on our earlier research experiences[1]. This study focused on the strategies for implementing practical activities in children with intellectual disabilities, with the goal of encouraging and rehabilitating neurophysiological processes of attention, behaviour, and cognition. It also focuses the concept of treatment and rehabilitation, based on the new strategies. Subject: The purpose of this study was to shed light on the cognitive and behavioural functioning of children with mild intellectual disabilities in relation to various aspects of the treatment strategies used. Study also present new strategies of treatment suggested for pandemic situation of Covid 19. Materials and Methods: The study sample included 124 participants with mild intellectual disability of both sexes, aged 8 to 13 years,from primary schools in Belgrade. In this research we applied the Trial Making Test (TMT; Reitan, 1971, Hamdan, Hamdan, 2009.) for attention assessment, the IOWA Conners’ Rating Scale for Children for behavior assessment, while for the assessment of cognitive function, the Test of Concept Utilization (TCU; Crager & Lane, 1989; Macesic-Petrovic, Kovacevic, Djuric-Zdravkovic, 2013.) was administered. Results: The findings show that more than half of the children surveyed have developmental disabilities in the areas studied. and a statistically significant correlation between the applied treatment modalities and tested abilities and functions (r = 0.52-0.59, p < 0.01). The study emphasises the importance of implementing a multimodal oriented approach.: team work of professionals and non-professionals (cooperation between professionals and parents), complementary treatment (medical and special treatment, psychosocial interventions, combination of treatment strategies), psychotherapy and psychopharmacotherapy when necessary, as well as special education rehabilitation, based on individual educational programs and individual training programs (IEP and ITP). It also focuses the treatment strategies in situation of Covid 19, because of it possible influence on the conclusion of the study. Conclusion: Finally, we proposed new treatment strategies with an emphasis on the special rehabilitation treatment and combination of strategy treatment, focuses to the new pandemic existential situation.